The Combination of Safety, Attractiveness, and Accessibility Lead to Bias in Inventory of Wetland Plants on the Qinghai‐Tibet Plateau - Yigang Li; Fan Liu; Meiying Gong; Xing Liu; Changchun Li (Ecology and Evolution)
ABSTRACT Assessments of inventory incompleteness often focus on terrestrial taxonomic groups, with less attention given to freshwater ecosystem groups. In this study, we constructed a wetland plant database for the Qinghai‐Tibet Plateau (QTP) and evaluated the inventory incompleteness of wetland plants. By combining three types of variables: safety, attractiveness, and accessibility, we identified the key drivers of inventory incompleteness and established priority areas for further investigation. The results showed that the inventory incompleteness of wetland plants on the QTP is relatively low, and the areas with incomplete inventories are mainly concentrated in the Himalayas and Hengduan Mountains. Safety variables emerged as the most important factors influencing inventory incompleteness, with landslide risk, slope, species richness, and livestock density identified as key variables affecting this incompleteness. We identified the southeastern Hengduan Mountains as a priority area for future wetland plant surveys. Specifically, the priority areas for future wetland plant collection are mainly distributed in the Qomolangma Region, the middle reaches of the Yarlung Zangbo River, the Nyenchen Tanglha Mountains–Eastern Himalayas, the transition zone between the Northern Tibetan Plateau and the Hengduan Mountains, and the Qionglai Mountains–Daxue Mountains–Shaluli Mountains. This study provides valuable references for future wetland plant sampling and conservation efforts on the QTP.